2018
DOI: 10.1155/2018/4651726
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin Inhibits Virulence Factors ofCandida albicans

Abstract: Candida albicans infections present a heavy burden upon public health, with only a few drugs available, while biofilms formed by C. albicans worsen this situation. Dioscin has antitumor, anti-inflammatory, and hepatoprotective effects, and this study was conducted to evaluate the effects of dioscin on the biofilm formation and development, as well as other virulence factors of C. albicans such as morphological transition, adhesion, and extracellular secreted phospholipase. Our results showed dioscin inhibits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 49 publications
(68 reference statements)
7
34
0
Order By: Relevance
“…The cell membrane-disruptive activity of dioscin may be due to the penetration into and accumulation in membrane lipid and the binding to ergosterol, a counterpart of cholesterol in fungal cells [41]. Recently, dioscin was found to be effective against the formation and development of C. albicans biofilms, a microbial lifestyle with complex structures and high resistance to antifungal agents [38, 42].…”
Section: Antifungal and Antiviralmentioning
confidence: 99%
“…The cell membrane-disruptive activity of dioscin may be due to the penetration into and accumulation in membrane lipid and the binding to ergosterol, a counterpart of cholesterol in fungal cells [41]. Recently, dioscin was found to be effective against the formation and development of C. albicans biofilms, a microbial lifestyle with complex structures and high resistance to antifungal agents [38, 42].…”
Section: Antifungal and Antiviralmentioning
confidence: 99%
“…Extracellular phospholipase of C. albicans , the expression of which was increased during C. albicans infections, can break down lipids of membrane for tissue invasion, while C. albicans mutants with phospholipase defects showed attenuated virulence in murine infection models [21, 24, 39, 40]. Our results showed that LH could inhibit the production of extracellular phospholipase.…”
Section: Discussionmentioning
confidence: 68%
“…The inhibition on biofilm formation could also be confirmed by CLSI images. The inhibition on preformed biofilms was weaker than that on biofilm formation, which can also be seen with many other antifungal agents [21, 24, 26]. This may be due to the condensed networks of intertwined hyphae and the existence of extracellular matrix, which compromise the access of drugs into cells within biofilms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the preclinical nature of these data, dioscin did show promising hepatoprotective effects on ALD, while published data suggest that its anti-inflammatory and anti-Candida (including anti-hyphal) activities may add to that effects. 4,5 The potential mechanisms need to be confirmed by more direct experimental evidence.…”
Section: The Potential Missing Links Between Hepatoprotective Dioscinmentioning
confidence: 99%